Business ethics and principles in the marketing industry: Systematic Literature Review - Nurul Hildha Afifa; Imam Mukhlis (Ethics and Law Journal: Business and Notary, 2023)
The aim of the research is to know the literature of business ethics and principles in industrial marketing searches are conducted on publications from 2019 to 2023 for scientific literature, utilizing exclusively open access journals. When "ethic, marketing and industry, ethic" was typed into a reference search, 449 journals came up. Subsequently, after going through the stage of filtering and obtaining 80 journals, there are 42 journals that are sought after, and 9 journals that satisfy the requirements for searching content and issues make up the final stage of the performance report. Business ethic and principle of business has an impact on industrial marketing. The finding in the literature inform to offer a set of ethical guidelines and business ethics principles that can be used in the marketing industry. The conceptual resources provided by the arguments proposed by the author as useful to stimulate further debate. In academic research, the two domains can be seen as different structures. In fact, marketing ethics emphasizes compliance with rules, values, and principles